2018
DOI: 10.1097/md.0000000000012670
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy obesity status and risks on pregnancy outcomes in Shanghai

Abstract: Obesity in women of reproductive age is not only associated with numerous adverse maternal and fetal effects prenatally but also exerts a negative influence on female fertility. The aim of this study was to investigate the situation of prepregnant obesity in Shanghai and explore the impact of prepregnant obesity on gestational weight gain as well as other pregnancy outcomes. A prospective hospital-based pregnant women cohort was established in Shanghai since January 2015. All pregnant women who were registered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
(19 reference statements)
1
3
0
1
Order By: Relevance
“…Prepregnancy BMI was significantly correlated with the need for cesarean section, which is also consistent with previous studies [40, 41]. It showed an inverse association with SGA in univariate and multiple regression analyses, in good agreement with a metanalysis by Goto et al and a study by Li et al [42, 43].…”
Section: Discussionsupporting
confidence: 91%
“…Prepregnancy BMI was significantly correlated with the need for cesarean section, which is also consistent with previous studies [40, 41]. It showed an inverse association with SGA in univariate and multiple regression analyses, in good agreement with a metanalysis by Goto et al and a study by Li et al [42, 43].…”
Section: Discussionsupporting
confidence: 91%
“…Pregnant women should have access to lifestyle and nutritional advice to manage weight gain during pregnancy. 173 The weight monitoring and guidance in pregnancy also need to be strengthened, and to establish the weight growth standard suitable for Chinese pregnant women is critical for scientific guidance of maternal nutrition.…”
Section: Maternal Nutritionmentioning
confidence: 99%
“…Studies described how obesity might predispose for maternal and fetal illnesses either before or during pregnancy. 21,22 On contrary, a previous study suggested that prepregnancy obesity has a protective effect associated with longer gestation duration and lower risk of preterm or low birth weight. 23 Insulin resistance increases during pregnancy especially during the last half of pregnancy.…”
mentioning
confidence: 92%